Design and fabrication of portable apron clothesline - Mohd Zambri, Abidin (2007)
Manufacturing process is a process of converting raw material into product. It can be described the transformation of materials into items of greater value by means of one or more processing and/or assembly operations. The study of manufacturing was very important in order to carry out this project to ensure that student understand on what are needs to do. This project is about designing and fabricating the Portable Apron Clothesline that can be used to hang the welding. The main objective in this project is to design an apron clothesline that is suite to its application special for welding apron in Faculty of Mechanical (FKM) Lab. This project involves the process of designing the clothesline by considering the shape, functionality, portability for people to use it and the manufacturing cost. The material of this design is easy to gain it, because it only using rectangular hollow steel and round steel. So that the method joining that can be compatible in assembled this clothesline is welding process. In assembled the wheel, fastening method is the best chosen because it's only use bolt and nut to bind the wheel with the base of this clothesline. This project also required analysis to ensure the strength and safety of the product meet the user need. After all processes had done, the development of this clothesline may help us to understand the fabrication and designing process involved in this project.-Author